Produção orgânica de cebola - Moraes, Rosa Maria Domingues (2009)
The present work had as objective to evaluate the effect of organic fertilizers Combinated with fitoprotectors in characteristics of onion plants. Two experiments were led to field in FEPAGRO/SUL, Rio Grande, RS, Brazil at august,11-21 December in two experiments in 2005/2006, utilizing the Petroline' onion (medium cycle)submitted to the treatments: T1 (15Mgha-1 vermicompost + SM 5% + UV 5% + CB 1%; T2 (15Mgha-1 vermicompost); T3 (30Mgha-1 bovine manure +SM 5% + UV 5% + CB 1%);T4 (30Mgha-1 bovine manure);T5 (45Mgha-1 vermicompost + SM 5% + UV 5% + CB 1%);T6 (45 Mgha-1 vermicompost); T7 (60Mgha-1 bovine manure + SM 5% + UV 5% + CB 1%); T8 (60Mgha-1 bovine manure)-Where: SM- Supermagro, UV- cattle Urine; CB- Calda bordalesa. the statistic utilized was a randomized blocks, with eigth treatments and four repetitions. After the analysis was applied the comparison of the averages by Duncan test. The variable studied were: Number of leaves for plants, planth eigth (cm), weigh of bulbs for class before the cure (g), weigh of bulbs for class after cure (g),commercial productivity in each treatment the organic fertilizer in onion made possible to obtain a superior productivity to average of the state, being shown that supermagro 5% + cattle urine % + calda bordalesa 1% showed a superior results in 2006.The great perceptual of bulbs of the harvested onions had been distributed we the classroom 3 (average bulbs)in all treatments in two experiments. O treatment T7 (60Mgha-1 bovine manure + SM 5% + UV 5% + CB 1%).